Chemical Imaging Beyond the Diffraction Limit: Experimental Validation of the PTIR Technique. Issue 3 (4th October 2012) - Lahiri, Basudev; Holland, Glenn; Centrone, Andrea
Abstract Photothermal induced resonance (PTIR) has recently attracted great interest for enabling chemical identification and imaging with nanoscale resolution. In this work, electron beam nanopatterned polymer samples are fabricated directly on 3D zinc selenide prisms and used to experimentally evaluate the PTIR lateral resolution, sensitivity and linearity. It is shown that PTIR lateral resolution for chemical imaging is comparable to the lateral resolution obtained in the atomic force microscopy height images, up to the smallest feature measured (100 nm). Spectra and chemical maps are produced from the thinnest sample analyzed (40 nm). More importantly, experiments show for the first time that the PTIR signal increases linearly with thickness for samples up to ≈ 1 μm (linearity limit); a necessary requirement towards the use of the PTIR technique for quantitative chemical analysis at the nanoscale. Finally, the analysis of thicker samples provides the first evidence that the previously developed PTIR signal generation theory is correct. It is believed that the findings of this work will foster nanotechnology development in disparate applications by proving the basis for quantitative chemical analysis with nanoscale resolution.